Promoting the modal shift of freight from road to rail in China: An evolutionary game and simulation study - Shuai Liu; Guangzhi Jia (PLoS ONE, 2025)
In the context of China’s road to rail policy, this study constructs a tripartite evolutionary game model to mathematically investigate the strategic interactions among local governments, railway transport enterprises, and shippers. By employing mathematical modeling and simulation analysis, we examine the dynamic evolution of each stakeholder’s strategy under varying conditions and verify the stability of the model. The findings indicate that government subsidies have a substantial effect on promoting shippers’ adoption of rail transport, although this effect weakens over time. Furthermore, improvements in service quality by railway enterprises can significantly increase the attractiveness of rail transport, with shippers demonstrating the capacity to swiftly adapt to changing market conditions. This research highlights that an initial phase of government subsidies, followed by their gradual withdrawal, can effectively facilitate the modal shift from road to rail by leveraging market mechanisms. This study provides theoretical insights and practical guidance for the formulation of effective transport policies, emphasizing the pivotal role of government incentives, the proactive engagement of railway enterprises, and the adaptive behavior of shippers in advancing sustainable freight transport.